2003
DOI: 10.1590/s0036-46652003000200007
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of histopathological findings in 894 cases of megacolon: what is the relationship between megacolon and colonic cancer?

Abstract: Patients with megaesophagus (ME) have increased prevalence of cancer of the esophagus. In contrast, a higher incidence of colorectal cancer is not observed in patients with megacolon (MC). MC is very common in some regions of Brazil, where it is mainly associated with Chagas disease. We reviewed the pathology records of surgical specimens of all patients submitted for surgical resection of MC in the Hospital das Clínicas of the Faculty of Medicine of Ribeirão Preto (HC-FMRP), from the University of São Paulo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
0
29
0
12
Order By: Relevance
“…Constipation is a major symptom of megacolon that may be caused by the intrinsic denervation of the viscera. Available human data have shown that intrinsic colonic denervation is protective against the development of colon tumors, but the reasons for this protection remain unknown (2,3). We have reported that colonic denervation due to chemical ablation of myenteric neurons (4) or due to Trypanosoma cruzi infection (5) is associated with a lower incidence of colonic cancer induced by a chemical carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a major symptom of megacolon that may be caused by the intrinsic denervation of the viscera. Available human data have shown that intrinsic colonic denervation is protective against the development of colon tumors, but the reasons for this protection remain unknown (2,3). We have reported that colonic denervation due to chemical ablation of myenteric neurons (4) or due to Trypanosoma cruzi infection (5) is associated with a lower incidence of colonic cancer induced by a chemical carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…Available clinical data strongly suggest the existence of protection against colon cancer in patients with megacolon due to Chagas' disease, which is caused by T. cruzi (3). However, the mechanisms for this protection against cancer development are not known.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although its incidence is declining, an impressive number of individuals still suffer from this disease, 1 and it has a wide distribution in Central and South America. It has been reported in all countries in the Americas, except in Canada.…”
mentioning
confidence: 99%